SEPTIC/UNSAFE ABORTION: A PREVENTABLE TRAGEDY - Sultana, Ruqqia; Noor, Shehla; Fawwad, Ali; Abbasi, Nasreen; Bashir, Rubina (Journal of Ayub Medical College Abbottabad, 2012)
Background: Unsafe abortion is one of the greatest neglected problems of health care in developing countries like Pakistan. In countries where abortions are restricted women have to resort to clandestine interventions to have an unwanted pregnancy terminated. The study was conducted to find out the prevalence of septic induced abortion and the associated morbidity and mortality and to highlight the measures to reduce it. Methods: This cross-sectional descriptive study was carried out in Obs/Gyn B Unit, Ayub Teaching Hospital, Abbottabad from January 2007 to December 2011. During this period all the patients presenting with pyrexia lower abdominal pain, vaginal bleeding, acute abdomen, septic or hypovolaemic shock after undergoing some sort of intervention for abortion outside the hospital were included. After thorough history, examination and detailed investigations including high vaginal and endocervical swabs for culture and sensitivity and pelvic ultrasound supportive management was given followed by antibiotics, surgical evacuation of uterus/ major laparotomy in collaboration with surgeon as required. Patients with DIC or multiple system involvement were managed in High Dependency Unit (HDU) by multidisciplinary team. Results: During the study period out of a total 6,906 admissions 968 presented with spontaneous abortion. There were 110 cases (11.36%) of unsafe abortion, 56.4% presented with vaginal discharge, 34.5% with vaginal bleeding, 21.8% with acute abdomen, while 18.9% in shock and 6.8% with DIC. Fortynine percent patients used termination as a method of contraception. Mortality rate was 16.36%, leading cause being septicaemia. Conclusion: Death and severe morbidity from unsafe abortions and its complications is avoidable through health education, effective contraception, early informed recognition and management of the problem once it occurs. Keywords: Abortion, unsafe, septic, DIC, Prevention